Subacute Toxicity Effects of the Aqueous Shoot Extract of Yushania alpina (K. Schum.) W.C.Lin in Sprague Dawley Rats: An Appraisal of Its Safety in Ethnomedicinal Usage - Joseph Ngugi Wanjiru; Timothy Elias Maitho; James Mucunu Mbaria; Gervason Apiri Moriasi (Journal of Toxicology)
Plant-based medicines have effectively managed several ailments in humans and animals since prehistoric times. However, the pharmacologic efficacy and safety of many plants currently used in traditional medicine have not been explored empirically, which raises serious public health concerns, derailing further research and their integration into the conventional healthcare system. Despite the longstanding ethnomedicinal usage of Yushania alpina shoot extract to treat inflammation, microbial infections, and diarrhoea, among other diseases, there is insufficient scientific data to appraise its toxicity profile and safety. Accordingly, we investigated the subacute toxicity of the aqueous shoot extract of Y. alpina in Sprague Dawley rats (both sexes) for 28 days based on the Organisation for Economic Cooperation and Development guideline 407. In this study, all the experimental rats treated orally with 40 mg/Kg BW, 200 mg/Kg BW, and 1000 mg/Kg BW of the aqueous shoot extract of Y. alpina remained normal, like the control group rats, and did not show any clinical signs of subacute toxicity, and no morbidity or mortality was recorded. Besides, the weekly body weight gains and the haematological and biochemical parameters of experimental rats orally administered with the studied plant extract at the tested doses and in the control group were comparable (P>0.05). No pathologic alterations in internal organs were observed following necroscopy. Further, the differences in weights of the liver, kidney, and spleen of experimental rats which were subacutely treated with the studied plant extract and the control rats were insignificant (P>0.05). Moreover, no histopathological changes were observed in tissue sections of the liver, kidney, and spleen obtained from all the experimental rats. Our findings demonstrate that the aqueous shoot extract of Y. alpina may be safe as it does not elicit subacute toxicity in Sprague Dawley rats. Further toxicological and pharmacological studies using other model animals and in clinical setups are encouraged to fully appraise the efficacy and safety of the studied plant extract.